2012
DOI: 10.1299/jamdsm.6.1168
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Underlay Stiffness on Cutting Profile of Polycarbonate Sheet during Wedge Indentation Process

Abstract: This paper reports on the cutting characteristics of a polycarbonate (PC) sheet stacked on a flexible underlay by a wedge indentation. In order to investigate the effect of underlay stiffness on sheared profile of PC sheet, the stiffness ratio k r in the thickness direction was varied. Indentation of a 42° center bevel blade into a 0.5mm thickness PC sheet that was stacked on the flexible underlay was carried out experimentally and numerically. Deformation profile of wedged PC sheet was observed by a CCD camer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Eq. 7As discussed previously, the cutting response of the 0.5mm PC sheet exchanges the mechanical stiffness of the underlay (Mitsomwang et al, 2012). The PC sheet subjected to wedge indentation was bent-up due to the sinking of the counter underlay.…”
Section: Cutting Load Characteristicsmentioning
confidence: 83%
See 1 more Smart Citation
“…Eq. 7As discussed previously, the cutting response of the 0.5mm PC sheet exchanges the mechanical stiffness of the underlay (Mitsomwang et al, 2012). The PC sheet subjected to wedge indentation was bent-up due to the sinking of the counter underlay.…”
Section: Cutting Load Characteristicsmentioning
confidence: 83%
“…As for solid sheet materials, there are several research papers on the cutting behavior of paperboard (Nagasawa et al, 2006;Chaijit et al, 2008), resin materials (Nagasawa et al, 2010a;Nagasawa et al, 2010b;Mitsomwang et al, 2012;Mitsomwang et al, 2014), and viscoelastic materials (McCarthy et al, 2007;McCarthy et al, 2010;Schuldt et al, 2016;Boisly et al, 2016). In addition, a few of experimental and numerical studies had have predicted the time-dependent deformation of viscoelastic materials (Theocaris, 1962;Emiri and Tschoegl, 1993;Kucuk et al, 2013;Okazawa et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Chaijit et al (2008) discussed the combination performance of underlay stiffness with respect to cutting characteristics of thin sheet against a wedge indentation, when changing the combination stiffness and yielding strength of the underlay. A combination of the edge shape of blade and the stiffness of underlay affected the load response and sheared profile of workpiece (Mitsomwang et al, 2012). Murayama et al (2003Murayama et al ( , 2004 have reported the cutting mechanism of a 42° wedge indentation into a 4mm thickness aluminum sheet using a trapezoidal cutting blade imitated as a crushed tip.…”
Section: Introductionmentioning
confidence: 99%
“…Before discussing the PSA sandwiched sheet cutting, it is necessary to reveal the deformation characteristics of a single bulk PSA sheet which is subjected to a wedge indentation. As for the solid sheet materials, there are several papers on the cutting behavior of laminated structure (Chaijit et al, 2008), resin material (Mitsomwang et al, 2012, Nagasawa et al, 2010a, 2010b and viscoelastic material (Boisly et al, 2016, McCarth et al, 2010. In addition, several numerical studies had been reported to predict the time-dependent deformation characteristics of viscoelastic materials (Kucuk et al, 2013, Okazawa et al, 2007.However, there are not almost research papers on the cutting characteristics and compressive flow behavior of the PSA sheet.…”
mentioning
confidence: 99%